Photodynamic Antifungal Activity of Hypocrellin A Against Candida albicans - Yang, Yijia; Wang, Chenglu; Zhuge, Yingzhi; Zhang, Jian; Xu, Ke; Zhang, Qilu; Zhang, Haijuan; Chen, Haiyan; Chu, Maoping; Jia, Chang (Frontiers in Microbiology, 2019)
Many studies have reported that hypocrellin A (HA) exhibits effective antimicrobial activities with proper irradiation. However, its antifungal activity and the involved mechanism have not been fully defined. In this study, HA-mediated cytotoxicity in Candida albicans cells was evaluated after antimicrobial photodynamic therapy (aPDT). The results showed that 1.0 μg/ml HA significantly decreased the survival rate of C. albicans cells with light illumination. Moreover, the ROS levels were also remarkably elevated by HA. Further study found that HA combined with illumination led to cell membrane potential depolarization and cell membrane integrity damage. To investigate the form of cell death, a series of apoptosis-related parameters, including mitochondrial transmembrane potential, metacaspase activity, DNA fragmentation, nuclear condensation, and cytosolic and mitochondrial calcium, were analyzed. Data showed that all the above mentioned apoptosis hallmarks were affected after treatment with HA, indicating that HA induced C. albicans cell apoptosis. Finally, HA-mediated aPDT was demonstrated to be low-toxic and effective in treating cutaneous C. albicans infections. This study highlights the antifungal effect and mechanism of HA-mediated aPDT against C. albicans and provides a promising photodynamic antifungal candidate for C. albicans skin infections.